What is veiling? - Amer, Sahar (Edinburgh : Edinburgh University Press, 2014)
Examines the practice of veiling in Muslim culture, discussing its history, its religious, social, and political significance, and its importance to both conservative and progressive Muslim women as a symbol of commitment to their beliefs. --Publishers description.
Includes bibliographical references (pages 219-224) and index.
Print version record.
Master record variable field(s) change: 050
Keywords: Hijab (Islamic clothing); Veils -- Religious aspects -- Islam; Muslim women -- Clothing; Hijab (Islamic clothing); Muslim women -- Clothing; Veils -- Religious aspects -- Islam; RELIGION / Islam / General; Electronic books